Characterization and Physical Propertiesof Terpene Compound in Citronella Essential oil as Sources of Antibacterial Perfume - Teuku Rihayat; Rizal Syahyadi; Hismendi Hismendi; Nelly Safitri; Aida Safitri (Politeknik Negeri Lhokseumawe, 2022)
ABSTRACTÂ Along with the development of modern industries such as the perfume, cosmetic, food, aromatherapy and pharmaceutical industries, the world's need for essential oils is increasing every year. Several parameters developed in this article include the effect of pressure (1, 2, 4, 6, 8) mmHg and time (20, 40, 60) minutes until final boiling point on the volume of oil produced and geraniol concentration. The analysis carried out was GCMS analysis and bacterial activity in the application of perfume products. From the research results it was found that at 1 atm pressure the geraniol concentration increased by 50% to 80.11%. Apart from these compounds, other compounds were also obtained such as citronellol, rhodinol and cheprol. at this pressure also produced the highest product volume of 21.2 ml. The application of the product resulting from the vacuum distillation process in the form of an anti-bacterial perfume at an incubation time of 48 hours has the strongest anti-bacterial activity with a diameter of 10.13 mm against Staphylococcus aureus bacteria.Keywords: Characterization, Citronella Oil, Vacuum Distillation, Perfume, Terpene